INFLUENCE OF PRICE AND NON-PRICE FACTORS ON THE RATIONALIZATION OF DOMESTIC WATER CONSUMPTION IN SAUDI ARABIA - S. H. Al-Kahtani (Journal of Animal and Plant Sciences, 2012)
This study aimed to analyze the most important factors in rationalizing the consumption of domestic water, and then identify the most appropriate water policies to be applied to maintain supply and consumption of domestic water. The study was mainly relying on primary data in the form of a questionnaire designed to achieve the objectives of the study. Descriptive statistical measures have been applied to assess the impact of some factors on the rationalization of water consumption, as well as the use the multinomial logit model to estimate the proportion of households water consumption, which is located in the various segments of the block price, and finally multi-regression model has been applied to estimate the average household consumption in different segments. The results revealed that 11% of the water consumers are affected by water conservation campaigns organized by the Ministry of water and electricity, while 58% (a high percentage) are not affected by the rationalization campaigns, which indicates that the voluntary policy is not feasible in the short term and that the ministry should search for complementary policy of water demand management to be more influential on the rationalization of water consumption.
Keywords: Water policies; Multinomial logit model; Complementary policy; Water demand management.